KRK DLA SZKOLNICTWA WYŻSZEGO W POLSCE JAKO OKAZJA DO PRZEKSZTAŁCEŃ W SFERZE KOMPETENCJI W GLOTTODYDAKTYCE. KOMUNIKAT Z WSTĘPNYCH BADAŃ NA TEMAT FORMUŁOWANIA I WALIDACJI EFEKTÓW KSZTAŁCENIA W RAMACH REFORMY SZKOLNICTWA WYŻSZEGO - Karpińska-Musiał, Beata (Neofilolog, 2019)
This article presents a theoretical discussion, supported by empirical research, about the attitudes of university teachers of foreign language in Poland towards the implementation of the National Qualification Framework for Higher Education. The opinions on the topic were collected by a questionnaire, conducted in March 2012, among representatives of 17 Polish universities. The research aimed to investigate whether institutional and administrative change connected with the reform of higher education in Poland is in any way contributing to reframing of competencies, or to the development of new competencies in foreign language teachers and researchers. The inter-nationalization of tertiary education and demands for orientation to the job market, widely discussed in literature and public debate recently, are irreversibly connected with globalization and the Bologna process. It is important to raise the question how this affects the generic and specific competencies of teacher trainers and educators. The research results revealed that academics are highly sceptical about the assumptions and effects of the implementation of the NQF. It is the author’s intention to diagnose the reasons for this in the context of seeing the NQF as creating new space for modi-fied and redefined skills, which are indispensable in the new educational reality.